On Monitoring of Liquid/Gas Flow Using Ultrasonic Tomography (Jurnal Teknologi (Sciences & Engineering), 2012)
In this paper, 16–pairs of ultrasonic sensors have been used. The system is capable of visualising the internal characteristics of liquid and gas flow, and provides the concentration map of the corresponding liquid and gas flow. The investigations were based on the transmission and reception of ultrasonic sensors that were mounted circularly on the surface of test pipe. Three experiments were carried out on the test pipe to simulate the horizontal flow of liquid (water) and gas (air) with three static conditions. The results showed that as the distance between the transmitting sensor and receiving sensor increases, the ultrasound will consume a longer travel time to reach to the target. Keywords: Ultrasonic, ultrasonic tomography, liquid and gas flow, flow measurement system